HEALTH BELIEF MODEL TO TUBERCULOSIS AND DRUG USE OF MYANMAR WORKERS: A QUALITATIVE STUDY - KAMNARAI, HATHAIKAN; CHIEWCHANTANAKIT, DARANEE (Thai Bulletin of Pharmaceutical Sciences, 2018)
การวิจัยนี้เป็นการวิจัยเชิงคุณภาพ มีวัตถุประสงค์เพื่ออธิบายแบบแผนความเชื่อด้านสุขภาพและการใช้ยาของผู้ป่วยวัณโรคปอดที่เป็นแรงงานชาวเมียนมาในอำเภอกระทุ่มแบน จังหวัดสมุทรสาคร ใช้วิธีการสัมภาษณ์เชิงลึกผู้ให้ข้อมูลสำคัญ โดยมีผู้ให้ข้อมูลสำคัญเป็นผู้ป่วยวัณโรคปอดที่เป็นแรงงานชาวเมียนมาผู้ได้รับการวินิจฉัยและขึ้นทะเบียนการรักษากับโรงพยาบาลกระทุ่มแบนจังหวัดสมุทรสาครจำนวน 15 ราย ผลการศึกษาพบว่า ผู้ให้ข้อมูลส่วนใหญ่มีการรับรู้ความเสี่ยงของการเป็นโรคมีการรับรู้ความรุนแรงของการเป็นโรค มีการรับรู้ประโยชน์ของการรักษาและการป้องกันโรค มีการรับรู้ต่ออุปสรรคในการรักษามีสิ่งชักนำให้เกิดการปฏิบัติมีแรงจูงใจด้านสุขภาพและมีปัจจัยร่วมด้านประชากรและด้านโครงสร้างพื้นฐานอันได้แก่ความรู้เรื่องโรคและประวัติการเจ็บป่วยที่ส่งผลไปถึงการรับรู้และการปฏิบัติตนด้านสุขภาพ โดยผู้ให้ข้อมูลมีการรับรู้และความรู้เกี่ยวกับวัณโรคเพิ่มมากขึ้นจากประสบการณ์การเจ็บป่วยเป็นวัณโรคของตัวเองผู้ให้ข้อมูลพร้อมที่จะปฏิบัติตนตามข้อมูลข่าวสารและคำแนะนำของเจ้าหน้าที่เพื่อให้ตนเองหายป่วยจากวัณโรคสามารถกลับมาทำงานและมีรายได้ตามปกติสำหรับผลการศึกษาเรื่องการใช้ยาพบว่าผู้ให้ข้อมูลส่วนใหญ่มีความเข้าใจเรื่องการใช้ยาให้ความร่วมมือในการใช้ยาสามารถใช้ยาได้อย่างถูกต้องตามที่แพทย์สั่ง พบว่ามีผู้ให้ข้อมูลส่วนน้อยเท่านั้นที่มีปัญหาจากการใช้ยารักษาวัณโรค พฤติกรรมการใช้ยารักษาวัณโรคของผู้ป่วยแรงงานชาวเมียนมาสามารถอธิบายได้ด้วยแบบแผนความเชื่อด้านสุขภาพโดยผู้ป่วยมีแรงจูงใจที่อยากจะหายป่วยจากวัณโรค ข้อมูลข่าวสารเรื่องโรคและการดูแลตนเองจากบุคลากรทางการแพทย์มีผลต่อพฤติกรรมการใช้ยาของผู้ป่วยโดยผู้ป่วยมีการใช้ยาถูกต้อง จดจำยาที่กินได้ และมีความร่วมมือในการใช้ยารักษาวัณโรคที่ดี The objective of this qualitative research was to explain the Health Belief Model and the pattern of drug use among Myanmar worker patients with Pulmonary Tuberculosis in Krathumbaen district, Samutsakhon province. The qualitative data were collected through in-depth interviews among the key informants, who were fifteen Myanmar workers with Pulmonary Tuberculosis being registered patients at Krathumbaen Hospital, Samutsakhon. This research has revealed that the majority of the key informants were aware of perceived susceptibility, perceived severity, perceived benefits and perceived barriers. Furthermore, the results have indicated that the key informants acquire cues of action, health motivation and modifying factors in terms of population and infrastructure, particularly knowledge of the disease and their own personal illness which caused relevant perception and health care practice. The key informants were reported to gain better awareness and knowledge on Tuberculosis from their own experience of the symptom. They were willing to abide with the given information and authorities’ recommendations regarding an appropriate treatment of Tuberculosis in order to cure themselves from the illness and back to normal working life to earn consistent income. In terms of their patterns of drug use, the study has discovered that most of the key informants gained adequate understanding of medicine application, cooperated in medication adherence and well cooperated to given medical instructions. Accordingly, only a few patients were found to have drug related problems of Tuberculosis treatment. In conclusion, the medical use behavior among Myanmar worker patients with Pulmonary Tuberculosis could be explained by using the Health Belief Model.The patients were highly determined to be cured from the symptom. Proper information on the symptom and appropriate advice from medical professionals affected positive medical use behaviors of the patients by promoting medical adherence for Tuberculosis treatment and accuracy of taking drugs.